Analysis of Waste Processing Technology on Community Willingness to Pay in Madiun City Using the Analytic Hierarchy Process (Case Study: Waste Processing at TPA Winongo, Madiun City) - Nurjayanti Nurjayanti; Mochamad Solikin; Purwanti Sri Pudyastuti (Eduvest - Journal of Universal Studies, 2025)
The objective of this study is to explore stakeholder perspectives on the prioritization of waste treatment technologies in Madiun City and to estimate the community's Willingness to Pay (WTP) for improved waste management services. This research utilized both primary and secondary data. Primary data for the Analytical Hierarchy Process (AHP) method were collected through 30 respondents using the Expert Choice application, targeting stakeholders involved in the waste management sector. Meanwhile, the WTP estimation was based on purposively sampled responses from 100 individuals—50 respondents from Manguharjo sub-district and 50 from Manisrejo sub-district. The results of the AHP analysis indicate that the highest priority waste treatment technology in Madiun City is controlled landfill, with a weight of 0.39, followed by composting at 0.36, and waste segregation at 0.25. The criteria and alternative evaluations were deemed consistent, as indicated by a Consistency Ratio (CR) of ≤ 0.1. In terms of WTP, the amount the community is willing to pay for the segregation method is relatively low, at less than IDR 2,000. This is in contrast to the composting method, where respondents are willing to pay more than IDR 2,000, and the highest WTP is observed for the controlled landfill method, exceeding IDR 3,000. The variation in WTP values is also influenced by demographic factors such as gender and occupation.